The Potential for Community Economic Development Through Mosque in Negeri Perak - Ahmad Muzammil Mohamed Shapawi (Sharia and Law Faculty, 2022)
The mosque holds a very important position for Muslims so that the mosque must be optimized in its operation. However, currently many mosques are limiting their functions to daily worship matters solely. Therefore, this article attempts to examine the economic development potential of the ummah through mosques. The focus of this study was carried out in three mosques in different regions, namely the Sultan Idris Shah II Mosque (National Mosque), the Sultan Idris Shah II Mosque (Regional Mosque) Slim River Perak and the Ar-Rashdiah During Perak Mosque. This study uses a qualitative method, namely by using a type of field research (field research) which is carried out in the form of interviews, observation and document analysis. The results of the study show that mosques in Negeri Perak have the potential to develop the people's economy on the condition that various mosques must be standardized in the form of preparing mosque financial accounts including mosque property records. Apart from that, there is also standardization of mosque committees for managers to master technology, standardization of accountability so that any information in the mosque must be available at the Regional Level (Regional Religion Department) and the Headquarters Level, namely the Mosque Management Division. This is to facilitate the supervision of the authorities in each mosque.Masjid memegang posisi yang sangat penting bagi umat Islam sehingga masjid harus dioptimalkan dalam pengoperasiannya. Namun, saat ini banyak masjid yang membatasi fungsinya pada urusan ibadah harian semata-mata. Oleh karena itu, artikel ini berusaha mengkaji potensi pengembangan ekonomi umat melalui masjid. Fokus kajian ini dilakukan di tiga buah masjid yang berbeda daerah yang berada di Negeri Perak, yaitu Masjid Sultan Idris Shah II (Masjid Negeri), Masjid Sultan Idris Shah II (Masjid Daerah) Slim River Perak dan Masjid Ar-Rashdiah Selama Perak. Penelitian ini menggunakan metode kualitatif yaitu dengan menggunakan jenis penelitian lapangan (field research) yang dilakukan dalam bentuk wawancara, observasi dan analisis dokumen. Hasil penelitian menunjukkan bahwa masjid di Negeri Perak berpotensi dalam pengembangan ekonomi umat dengan syarat berbagai masjid harus distandardisasi berupa menyiapkan rekening keuangan masjid termasuk catatan properti masjid. Selain itu, juga standardisasi kepanitian masjid bagi pengelola agar menguasai teknologi, standardisasi akuntabilitas agar setiap informasi yang ada di masjid harus ada di Tingkat Daerah (Departmen Agama Daerah) dan Tingkat Markas yaitu Bahagian Pengurusan Masjid. Hal ini untuk memudahkan pengawasan pihak berwenang di masing-masing masjid.